Correlation of Biomechanical Properties and Grayscale of Articular Cartilage using Low-Field Magnetic Resonance Imaging - Wansin, Yew; Juzaila Abd Latif Yew, Mohd; Majedah Idrus Alhabshi, Sharifah; Mahmud, amaluddin; Rafiq Abdul Kadri, Mohammed (International Journal of Engineering and Technology, 2018)
Osteoarthritis is a joint disease that caused by the progression of degenerative articular cartilage tissue. The degeneration of the articular cartilage resulted in alteration of the biomechanical properties. Magnetic resonance imaging (MRI) has become the most potential imaging technique to assess the condition of the articular cartilage. However, most of the previous studies of articular cartilage were performed using high-field MRI units. Therefore, this study aimed to examine the correlation between the biomechanical properties of articular cartilage and the image grayscale using low-field MRI. Cartilage specimens extracted from bovine femoral head were scanned using 0.2 T MRI to obtain the cartilage image. The MRI image was characterized based on the intensity of grayscale. Indentation test was then conducted on the specimen to characterize the cartilage biphasic properties of elastic modulus and permeability. The cartilage grayscale values were moderately correlated with cartilage biphasic elastic modulus and higher correlation was observed with the permeability. These could indicate the potential application of low-field MRI to evaluate the biomechanical properties of articular cartilage.Â